ANALISIS PENGARUH KUALITAS PELAYANAN, KEPUASAN PELANGGAN, DAN NILAI PELANGGAN DALAM MENINGKATKAN LOYALITAS PELANGGAN ASRI MOTOR - Safitri, Saptianipo Aprilia; Sugiono, Sugiono (Diponegoro Journal of Management, 2015)
The aims of this research are to determine the effects of service quality, customer satisfaction, and customer value toward the customer loyalty of Asri Motor Semarang.            The Variable in this study consists of four variable, where in the first stage the variable customer satisfaction and customer value into a variable-free, while customer satisfaction variable will be variables bound. Then in the second stage variable service quality, customer satisfaction and customer value into a variable of mediation. The sample in this study of 100 respondents ( Customer of Asri Motor Semarang ). Samples taken with the accidental sampling techniques. Then the data collected through questionnaires conducted tests of validity and reliability, continued with the normality of data and path analysis.            Results of analysis showed that the quality of service : direct or indirect effect on customer loyalty (through customer satisfaction ). The variable quality of service directly most of its influence on customer satisfaction and customer loyalty. While the value  of customers is the variable that most directly affects small towards customers satisfaction and customer loyalty. Then indirectly influence  the quality of service greater its effect on customer loyalty, through the mediation of customer satisfaction rather than variable to value costumers.